(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Mastitis is considered as an economically important disease of dairy buffaloes in Asia. This study examined the mastitis milk and nasal swab samples for the detection and genotyping of methicillin-resistant Staphylococcus aureus (MRSA) in water buffaloes. Materials and Methods: Staphylococcus aureus was identified based on biochemical tests and Polymerase Chain Reaction (PCR) detection of nuc gene, whereas MRSA on mecA gene. The disc diffusion test was used to determine the antibiotic resistance and staphylococcal cassette chromosome mec (SCCmec), spa, and multilocus sequence typing for the genotyping of isolates. Results: Staphylococcus aureus was detected on 39/93 milk (41.94%) and 27/384 nasal swab (7.03%) samples. However, only nine isolates (23.08%) harbored the mecA gene from milk samples and three isolates (11.11%) from the nasal carriage. All MRSA isolates exhibited resistance to cefoxitin and penicillin, whereas 50% were found resistant to clindamycin. All these isolates were found susceptible to sulfa-trimethoprim and chloramphenicol, whereas the majority of the isolates were susceptible to gentamicin, ciprofloxacin, tetracycline, and rifampicin. The SCCmec types of the MRSA isolates were type IVc (50.00%), type II (8.33%), type I (8.33%), and non-typeable (33.33%). The spa types and sequence type (ST) identified were t019 (ST30), t701 (ST1649), t311 (ST5), t657 (ST1148), t015 (ST508), t1939 (ST12), t800 (ST9), t091 (ST2454), t138 (ST5991), and t1642 (ST5992). Conclusion: Milk and nasal swab samples from dairy water buffaloes were found positive for MRSA. The MRSA isolates were still susceptible to most antibiotics tested. Moreover, the genotypes of some MRSA isolates were found similar to some human MRSA strains, suggesting a possible human to animal transmission. J. Adv. Vet. Anim. Res., 7(3): 397-406, Sep 2020 http://doi.org/10.5455/javar.2020.g434